An Upper Paleolithic Perforated Red Deer Canine With Geometric Engravings From QG10, Ningxia, Northwest China - Zhang, Yue; Doyon, Luc; Peng, Fei; Wang, Huimin; Guo, Jialong; Gao, Xing; Zhang, Shuangquan (Frontiers in Earth Science, 2022)
Personal ornaments are key archaeological remains to investigate prehistoric symbolic systems, and, whenever hard animal remains were used for their manufacture, explore topics on the status attributed to faunal resources by past human groups. Since the onset of the Upper Paleolithic, animal tooth pendants have been widely used in Eurasia as personal adornments or grave goods. However, only two Late Paleolithic Chinese sites have yielded such adornment types until today, i.e., Zhoukoudian Upper Cave, near Beijing, and Xiaogushan, in the Liaoning Province. Here, we present results from the multidisciplinary analysis of a perforated animal tooth from QG10, a multi-stratified archaeological site located on the Ordos Plateau between the arid and sub-arid belts of Northwest China. Although only partially preserved, zooarchaeological analysis indicates the tooth is a right upper canine of a female red deer (Cervus elaphus). Scraping marks on the labial aspect suggest the tooth was extracted from the animal maxillary shortly after its death. Technological analysis of the perforation confirms it was made by rotation with the help of a lithic point hafted onto a drill. The root and occlusal aspect of the tooth were further modified with five sets of notches and incisions, including four incisions making a hashtag pattern on the occlusal aspect. Technological and morphometric analyses indicate these sets were made by two, perhaps three, individual, i.e., one left-handed and one, perhaps two right-handed, with different tools and techniques. Use wear analysis suggests that the adornment was affixed to the body with the tooth crown facing upward. Finally, chemical characterization of red and black residues still adhering to the root indicates that hematite and charcoal may have been used in the production of an adhesive that would have helped stabilize the personal ornament on the body. Collectively, our results and interpretations shed a new light on the complexity of Late Glacial symbolic system carried by populations living in Northern China. We argue this perforated red deer tooth was introduced through the site following a number of social exchanges over long distance and a long period of time rather than produced in situ.